Building Numeracy Interest and Ability: The Effectiveness of Digital Simulation Media for Junior High School Students - Irsyad, Aan Nur; Setyaningrum, Wahyu (Universitas Muhammadiyah Mataram, 2026)
Low numeracy skills and declining learning interest among junior high school students represent a critical challenge in modern mathematics education. Traditional teaching methods often fail to bridge the gap in student engagement within increasingly digital learning environments. While digital simulations offer significant interactive potential to address these issues, their focused development and empirical testing for specific numeracy interventions remain insufficient. This study aimed to develop digital simulation media and evaluate its validity, practicality, and effectiveness in improving numeracy skills and learning interest independently. Using a Research and Development (R&D) approach with the ADDIE model, the media was tested on 32 eighth-grade students at an Indonesian public junior high school. Data were collected through numeracy tests, interest questionnaires, practicality assessments, and expert validation sheets. After confirming the normality assumption via Shapiro-Wilk, data analysis was conducted using paired sample t-tests and N-Gain scores. The results indicated that the media was deemed highly valid by both material and media experts. Teachers and students rated the media as